Social Inclusion and Exclusion for First Nations LGBTIQ+ People in Australia - Soldatic, Karen (2021)
This thematic issue of Social Inclusion highlights the connections between First Nations LGBTIQ+ people’s intersecting identities and inclusionary and exclusionary process in settler-colonial Australia. In this editorial, we briefly introduce key concepts and summarise the different contributions in the issue, providing some general conclusions and guidance on a possible future research agenda.